Method for preparing stable polyoxymethylene copolymer (CPOM)
By using triisopropanolamine and acid catalyst to form a complex in the preparation of polyformaldehyde copolymer, the problem of insufficient deactivation of the acid catalyst is solved, the thermal stability and hydrolytic stability of the polymer are improved, and formaldehyde emission is reduced , making it suitable for food or drinking water contact applications.
Patent Information
- Application Number
- CN201980046877.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-13
- Filing Date
- 2019-07-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-07-10
AI Technical Summary
In the prior art, when preparing polyformaldehyde copolymers, the acid catalyst is insufficient inactivation, resulting in insufficient thermal stability, hydrolytic stability and formaldehyde emission of the polymer, and cannot be suitable for food or drinking water contact applications.
During the preparation of polyformaldehyde copolymer, triisopropanolamine is used to form a complex with an acid catalyst to inactivate it, thereby improving the thermal stability and hydrolytic stability of the polymer and reducing the formaldehyde emission.
The polyformaldehyde copolymers exhibit improved thermal stability, hydrolytic stability and low formaldehyde emissions by deactivated acid catalysts by triisopropanolamine, suitable for food or drinking water contact applications.
Smart Images

Figure FDA0004754095640000011 
Figure FDA0004754095640000012 
Figure FDA0004754095640000021
Abstract
Description
Technical Field
[0001] The present invention relates to a method for deactivating an acid catalyst in a method for preparing a polyoxymethylene copolymer (cPOM) by adding triisopropanolamine (tris(2-hydroxypropyl)amine) to a mixture containing a polyoxymethylene copolymer (cPOM) and an acid catalyst.
[0002] Furthermore, the present invention relates to the use of triisopropanolamine for deactivating acid catalysts in the preparation of polyoxymethylene copolymers (cPOM).
[0003] Furthermore, the present invention relates to a process for preparing a polymer molding composition (PM) comprising a polyoxymethylene copolymer (cPOM), a polymer molding composition (PM) obtained by the preparation process and the use of the polymer molding composition (PM) for preparing a molding. Background Art
[0004] Polyoxymethylene copolymers have long been known. The polymers have many outstanding properties, so they are suitable for a variety of industrial applications. Polyoxymethylene copolymers are thermoplastic engineering plastics that can be used in various applications in the transportation, electrical, electronic and consumer industries. Polyoxymethylene copolymers are also called acetal resins, polyacetals and polyoxymethylene. In order to prepare polyoxymethylene copolymers, formaldehyde is usually converted into its cyclic oligomers, preferably 1,3,5-trioxane. Polyoxymethylene copolymers can be obtained by polymerizing cyclic oligomers of formaldehyde, preferably 1,3,5-trioxane, with one or more comonomers in the presence of an acid catalyst. The polymerization can be carried out in bulk polymerization, for example in a melt kneader. After the polymerization reaction, a crude polyoxymethylene copolymer that still contains the acid catalyst is obtained. If the acid catalyst remains in the polyoxymethylene copolymer, it can catalyze the depolymerization reaction of the polyoxymethylene copolymer to form formaldehyde, which produces unstable polyoxymethylene copolymers, which have very limited availability.
[0005] Therefore, after the polymerization, the acid catalyst is generally deactivated, and the crude polyoxymethylene copolymer is generally further stabilized by removing residual monomers and removing unstable terminal groups to obtain the final polyoxymethylene copolymer.
[0006] In order to deactivate the acid catalyst contained in the crude polyoxymethylene copolymer, a deactivator is usually added to the crude polyoxymethylene copolymer. As the deactivator, a basic compound is usually used. The basic compound used as the deactivator usually forms an acid-base product, in other words, a complex of the acid catalyst and the basic compound remaining in the polymer matrix of the polyoxymethylene copolymer.
[0007] German patent application DE 3 703 790 discloses a process for preparing polyoxymethylene copolymers in which the acid catalyst is deactivated using triethylamine, triethanolamine or tri-n-butylamine.
[0008] European patent application EP 1 688 461 also discloses a process for preparing polyoxymethylene copolymers in which the acid catalyst is deactivated by adding an amine, namely triethylamine.
[0009] European patent application EP 0 244 245 discloses a process for preparing polyoxymethylene copolymers in which the acid catalyst is deactivated using a hindered heterocyclic amine.
[0010] German patent application DE 196 33 708 discloses a process for preparing polyoxymethylene copolymers in which the acid catalyst is deactivated using ammonia, trimethylamine, dimethylamine or triethylamine.
[0011] US Pat. No. 7,893,140 discloses a method for preparing polyoxymethylene copolymers, wherein the acid catalyst is deactivated using triethylamine, tributylamine, triethanolamine or tributanolamine.
[0012] International Patent Application WO 93 / 22359 discloses a method for preparing a polyoxymethylene copolymer by copolymerizing trioxane as a main monomer and a cyclic ether or cyclic formal as a comonomer using a cation-active catalyst, wherein after the copolymerization is completed, an alkali metal fluoride is brought into contact with the copolymer to deactivate the polymerization catalyst.
[0013] However, the methods for preparing polyoxymethylene copolymers and deactivators used in the prior art result in the final polyoxymethylene copolymers showing insufficient stability in some cases. In addition, in some cases, the polyoxymethylene copolymers obtained by the preparation methods described in the prior art show too high a formaldehyde release, so that the final polyoxymethylene copolymers cannot be used for food or drinking water applications. In addition, in some cases, the polyoxymethylene copolymers obtained by the methods described in the prior art show migration of the deactivator, so that these polyoxymethylene copolymers cannot be used for food contact or drinking water applications. Summary of the invention
[0014] It is therefore an object of the present invention to provide a process for deactivating acid catalysts in a process for preparing polyoxymethylene copolymers which results in polyoxymethylene copolymers which do not have the above-mentioned disadvantages of the prior art or which have only a significantly reduced extent. In particular, the process should result in polyoxymethylene copolymers which exhibit improved thermal and hydrolytic stability, lower formaldehyde emissions and good color values as well as good mechanical properties and are at the same time suitable for food contact or drinking water applications.
[0015] The object is achieved by a method for deactivating an acid catalyst in a method for preparing a polyoxymethylene copolymer (cPOM), wherein the method for deactivating the acid catalyst comprises the following steps:
[0016] a) providing a first mixture (M1) comprising a polyoxymethylene copolymer (cPOM) and an acid catalyst,
[0017] b) adding triisopropanolamine to the first mixture (M1) to deactivate the acid catalyst to obtain a second mixture (M2) comprising a polyoxymethylene copolymer (cPOM) and a complex of the acid catalyst and triisopropanolamine.
[0018] Another object of the present invention is a polymer molding composition (PM) obtainable by the process according to the invention.
[0019] Surprisingly, it has been found that the properties of polyoxymethylene copolymers (cPOM) are improved if triisopropanolamine is used to deactivate the acid catalyst in the process for preparing polyoxymethylene copolymers (cPOM). The polyoxymethylene copolymers (cPOM) exhibit improved thermal and hydrolytic stability, lower formaldehyde emission, good color values and good mechanical properties.
[0020] Furthermore, it has surprisingly been found that the complex of the acid catalyst and triisopropanolamine remaining in the final polyoxymethylene copolymer (cPOM) is stable, so that the final polyoxymethylene copolymer (cPOM) is thermally stable, hydrolytically stable, shows lower formaldehyde emission, lower deactivator migration, and is therefore particularly suitable for applications requiring contact with food or drinking water. DETAILED DESCRIPTION
[0021] First mixture (M1)
[0022] In step a), a first mixture (M1) is provided, which comprises a polyoxymethylene copolymer (cPOM) and an acid catalyst.
[0023] Polyoxymethylene copolymers (cPOM) are known per se. They are preferably prepared by polymerization of trioxane (as monomer) and one or more comonomers.
[0024] Typically, the polyoxymethylene copolymer (cPOM) contained in the first mixture (M1) contains 60 to 99.99 mol % of -CH2O- repeating units and 0.01 to 40 mol % of repeating units of formula (I)
[0025]
[0026] Where R 1 To R 4 are each independently a hydrogen atom, a C1-C4-alkyl group or an alkoxy-substituted alkyl group having 1 to 4 carbon atoms, and R 5is a chemical bond, -CH2-, -OCH2-, a C1-C4-alkyl-substituted or C1-C4-alkoxy-substituted methylene or a corresponding oxymethylene group, and n is 0 to 3, wherein the mol% of the -CH2O- repeating unit and the mol% of the repeating unit of formula (I) are based on the total moles of the repeating units contained in the polyoxymethylene copolymer (cPOM).
[0027] Preferably, the polyoxymethylene copolymer (cPOM) contains 60 to 99.99 mol %, more preferably 80 to 99.95 mol %, even more preferably 90 to 99.9 mol % and particularly preferably 94 to 99.5 mol % of -CH2O- repeating units. Preferably, the polyoxymethylene copolymer (cPOM) contains 0.01 to 40 mol %, more preferably 0.05 to 20 mol %, even more preferably 0.1 to 10 mol % and particularly preferably 0.5 to 6 mol % of repeating units of formula (I), wherein the mol % in each case is based on the total number of moles of repeating units contained in the polyoxymethylene copolymer (cPOM).
[0028] Therefore, another object of the present invention is a process, wherein the polyoxymethylene copolymer (cPOM) comprises 60 to 99.99 mol % of -CH2O- repeating units and 0.01 to 40 mol % of repeating units of formula (I),
[0029]
[0030] Where R 1 To R 4 are each independently a hydrogen atom, a C1-C4-alkyl group or an alkoxy-substituted alkyl group having 1 to 4 carbon atoms, and R 5 is a chemical bond, -CH2-, -OCH2-, a C1-C4-alkyl-substituted or C1-C4-alkoxy-substituted methylene or a corresponding oxymethylene group, and n is 0 to 3.
[0031] The -CH2O- repeating units are generally introduced into the polyoxymethylene copolymers (cPOM) by polymerization of at least one main monomer selected from cyclic formals (cyclic oligomers of formaldehyde), with 1,3,5-trioxane being particularly preferred.
[0032] The recurring units of formula (I) can be advantageously introduced into the polyoxymethylene copolymer (cPOM) by ring-opening polymerization of at least one first comonomer selected from formula (II),
[0033]
[0034] Where R 1 To R 5 and n are as defined above in formula (I).
[0035] Preferably, the at least one first comonomer is selected from ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, 1,3-butylene oxide, 1,3-dioxane, 1,3-dioxolane and 1,3-dioxepane, with 1,3-dioxolane being particularly preferred.
[0036] Optionally, the polyoxymethylene copolymer (cPOM) may comprise repeating units derived from at least one second comonomer. The second comonomer is preferably selected from a cyclic ether of formula (III) or an acetal of formula (IV),
[0037]
[0038] Wherein Z is a chemical bond, -O-, -ORO- (R is C1-C8-alkylene or C3-C8-cycloalkylene), linear oligoformaldehyde and polyoxymethylene. Preferred second comonomers are selected from ethylene diglycide, diglycidyl ether, diethers derived from glycidyl and formaldehyde, dioxane or trioxane in a molar ratio of 2:1, and diethers derived from 2 moles of glycidyl compounds and 1 mole of aliphatic diols having 2 to 8 carbon atoms, such as diglycidyl ethers of ethylene glycol, 1,4-butanediol, 1,3-butanediol, cyclobutane-1,3-diol, 1,2-propylene glycol, 1,3-propylene glycol, cyclohexane-1,4-diol.
[0039] If at least one second monomer is used, the second monomer is preferably used in such an amount that the content of repeat units derived therefrom in the polyoxymethylene copolymer (cPOM) is 0.001 to 5%, preferably 0.01 to 2%, the mole % being in each case based on the total molar number of repeat units contained in the polyoxymethylene copolymer (cPOM).
[0040] By using at least one chain transfer agent (CTA), the molecular weight of the cPOM is adapted to the desired melt viscosity of the resulting product. As CTA, linear paraformaldehydes such as dimethoxymethane, diethoxymethane or dibutoxymethane can be used. Dimethoxymethane (CH3OCH2OCH3) is the preferred CTA.
[0041] The melting point of the polyoxymethylene copolymer (cPOM) contained in the first mixture (M1) is preferably 150 to 200° C., more preferably 160 to 180° C. The melting point of cPOM is determined according to DIN EN ISO 11357-3 (2013-04) at a heating and cooling rate of 20 K / min, with a sample weight of about 8.5 mg.
[0042] The molecular weight (weight average Mw; determined as described below) of the polyoxymethylene copolymer (cPOM) contained in the first mixture (M1) can be adjusted within a wide range. wPreferably, the molecular weight is 10 000 to 240 000 g / mol ± 10%, and the number average molecular weight M n Preferably, the molecular weight (Mw) of the polyoxymethylene copolymer (cPOM) contained in the first mixture (M1) is from 80 000 to 220 000 g / mol ± 10%, and the molecular weight (M n ) is preferably 9 000 to 38 000 g / mol. The polyoxymethylene copolymer (cPOM) contained in the first mixture (M1) preferably has an Mw / Mn ratio (polydispersity index) of 1.4 to 14, more preferably an Mw / Mn ratio of 2.1 to 14.
[0043] The molecular weights of polymers and cPOM were determined by size exclusion chromatography in a SEC apparatus (size exclusion chromatography). The SEC apparatus consisted of a combination of separation columns: a primary column of 5 cm in length and 8 mm in diameter, a second linear column of 30 cm in length and 7.5 mm in diameter. The separation material in the two columns was PL-HFIP gel purchased from Polymer Laboratories. The detector used included a differential refractometer purchased from Agilent 1100. A mixture consisting of hexafluoroisopropanol and 0.05% potassium trifluoroacetate was used as eluent. The flow rate was 1 ml / min and the column temperature was 35°C. 60 microliters of a solution with a concentration of 1.5 g of sample per liter of eluent was injected. The sample solution had been previously filtered through Millipor Millex FG (pore size 0.2 microns). Calibration was performed using narrow distribution PMMA standards with a molecular weight M of 800 to 2.220.000 g / mol purchased from PSS (Mainz, DE). The polydispersity index is defined as the weight average molecular weight divided by the number average molecular weight.
[0044] The molecular weight distribution of the polyoxymethylene copolymer (cPOM) contained in the first mixture (M1) may be unimodal or substantially unimodal. It may also have a multimodal molecular weight distribution. The cPOM may have a bimodal molecular weight distribution.
[0045] In step a), a first mixture (M1) is provided, which comprises a polyoxymethylene copolymer (cPOM) and an acid catalyst. In the present invention, the term "acid catalyst" is understood to mean exactly one acid catalyst and a mixture of two or more acid catalysts. Preferably, the first mixture (M1) comprises one acid catalyst. Furthermore, in the present invention, the term "acid catalyst" is understood to include the acid catalyst itself and the catalytically active conversion products of the acid catalyst.
[0046] The acid catalyst may preferably be at least one (e.g., two), more preferably one, halide of boron, tin, titanium, phosphorus, antimony or arsenic. Therefore, it may be preferred that the halide is a chloride or a fluoride, or that the halide comprises both a chloride and a fluoride. Examples thereof are boron trifluoride, tin tetrachloride, titanium tetrachloride, phosphorus pentafluoride, phosphorus pentachloride, antimony pentafluoride and arsenic pentafluoride, and especially complex compounds thereof.
[0047] The acid catalyst may preferably be at least one boron halide, in particular boron trifluoride, such as trifluoride boron hydrate, or at least one, more preferably one, coordination compound of a boron halide, and at least one, more preferably one, organic compound comprising at least one oxygen atom or sulfur atom or both. Thus, it may be more preferred that the organic compound comprises only at least one, in particular one, oxygen atom. The organic compound forming the coordination compound of the boron halide may be, for example, an alcohol, an ether or a sulfide.
[0048] Preferably, the acid catalyst is selected from boron halides coordinated with ethers, in particular alkyl ethers, such as C1 to C4 alkyl ethers being most preferred. Coordination compounds of boron trifluoride with ethers, in particular dialkyl ethers (e.g. C1 to C4 dialkyl ethers) may be most preferred, in particular boron trifluoride dibutyl etherate, boron trifluoride diethyl etherate or boron trifluoride dimethyl etherate or mixtures thereof. Most preferably, boron trifluoride diethyl etherate is used.
[0049] Therefore, another object of the present invention is a process, wherein the acid catalyst is at least one acid catalyst selected from boron trifluoride, a coordination complex of boron trifluoride with water, a coordination complex of boron trifluoride with a dialkyl ether, and catalytically active conversion products of the above acid catalysts.
[0050] In a particularly preferred embodiment, the first mixture (M1) comprises boron trifluoride diethyl etherate as acid catalyst.
[0051] The amount of the acid catalyst in the first mixture (M1) is not particularly limited. Typically, the amount of the acid catalyst in the first mixture (M1) is from 10 to 150 ppm, preferably from 20 to 140 ppm, more preferably from 30 to 130 ppm, and particularly preferably from 40 to 100 ppm, in each case based on the total weight of the main monomers and comonomers, preferably based on the total weight of the first mixture. Lower amounts may result in a slower initiation of the reaction, while higher amounts generally do not result in a faster reaction.
[0052] In a preferred embodiment, providing the first mixture (M1) in step a) comprises step a1), i.e., polymerization of at least one main monomer selected from cyclic formals, preferably 1,3,5-trioxane, and at least one first comonomer selected from formula (II) and optionally at least one second comonomer in the presence of an acid catalyst.
[0053] Therefore, another object of the present invention is a method, wherein step a) comprises the following steps:
[0054] a1) polymerization of at least one main monomer selected from cyclic formals and at least one first comonomer selected from formula (II) and optionally at least one second comonomer in the presence of an acid catalyst to provide a first mixture (M1) comprising a polyoxymethylene copolymer (cPOM) and an acid catalyst,
[0055]
[0056] Where R 1 To R 5 and n are as defined above.
[0057] Typically, the polymerization in step a1) can be carried out using a variety of methods. Said methods are known to those skilled in the art or can be obtained by applying the common sense of those skilled in the art. Preferably, the first mixture (M1) is prepared by cationic polymerization. During the cationic polymerization, the cPOM can be formed in bulk (i.e., without or substantially without the use of solvent).
[0058] The polymerization reaction can be carried out at a temperature, pressure and apparatus generally known to those skilled in the art, or at a temperature, pressure and apparatus obtainable by those skilled in the art by applying their common sense. For example, it can be carried out in an extruder or in a cascade of two or more extruders, such as a twin-screw type, such as a self-cleaning type. The method disclosed herein can also be carried out in a kneader or in a cascade of two or more kneaders, such as a self-cleaning type. Generally, it is advantageous to carry out the polymerization at the lowest possible temperature to avoid energy waste, and to carry out at a sufficiently high temperature to maintain the polymerization and ensure good blending, in particular by maintaining at least one monomer and at least one comonomer (if present) in a liquid state. Therefore, it is preferred to carry out the polymerization at a temperature of 50 to 150° C., wherein a temperature of 60 to 120° C. may be more preferred. Therefore, the temperature refers to the temperature in the body.
[0059] In one embodiment, the first mixture (M1) may further comprise 2 to 30% by weight of unreacted residual monomers. The unreacted residual monomers are generally selected from the above-mentioned main monomers, comonomers and formaldehyde.
[0060] In a preferred embodiment, the first mixture (M1) comprises
[0061] 70 to 98% by weight of polyoxymethylene copolymer (cPOM),
[0062] 2 to 30% by weight of unreacted residual monomers, and
[0063] 10 to 150 ppm of catalyst,
[0064] Based on the total weight of the first mixture.
[0065] According to step b), triisopropanolamine is added to the first mixture (M1) to deactivate the acid catalyst and obtain a second mixture (M2) comprising a complex of a polyoxymethylene copolymer (cPOM), an acid catalyst and triisopropanolamine.
[0066] The CAS number of triisopropanolamine (tri(2-hydroxypropyl)amine; TIPOA) is 122-20-3. Its molar mass is 191.27 g / mol, its melting point is 45° C., and its boiling point is 301° C. Triisopropanolamine is water-soluble.
[0067] In step b), triisopropanolamine can be added in pure form or in the form of a solution comprising triisopropanolamine and an organic solvent. Preferably, in step b), triisopropanolamine is added to the first mixture in the form of a solution comprising triisopropanolamine and an organic solvent. Suitable organic solvents are, for example, cyclohexane, methanol, ethanol, acetone, methyl ethyl ketone, ethyl acetate or benzene, wherein benzene and ethyl acetate are preferred. Ethyl acetate is most preferred.
[0068] If triisopropanolamine is added in the form of a solution, the concentration of triisopropanolamine is generally 1 to 50% by weight, preferably 5 to 60% by weight, more preferably 2 to 30% by weight and particularly preferably 3 to 10% by weight, based on the total weight of the solution comprising triisopropanolamine and the organic solvent.
[0069] Furthermore, in step b), in another embodiment, triisopropanolamine can be added in the form of a mixture with at least one other deactivator selected from ammonia, triethylamine, tri-n-butylamine and triethanolamine. However, in a preferred embodiment, in step b), triisopropanolamine is the only deactivator added.
[0070] In step b), triisopropanolamine is preferably added in a molar excess of 25:1 to 1:1, more preferably 10:1 to 1.1:1 and particularly preferably 5:1 to 1.2:1 relative to the acid catalyst contained in the first mixture (M1).
[0071] In step b), a second mixture (M2) is obtained, which comprises the polyoxymethylene copolymer (cPOM) and a complex of an acid catalyst and triisopropanolamine.
[0072] With regard to the polyoxymethylene copolymer (cPOM) and further optionally contained components, such as unreacted residual monomers, the above statements and preferences apply analogously.
[0073] Another object of the present invention is the use of triisopropanolamine for deactivating acid catalysts in the preparation of polyoxymethylene copolymers.
[0074] Preferably, triisopropanolamine is used after the polymerization step in preparing the polyoxymethylene copolymer.
[0075] Another object of the present invention is a method for preparing a polymer molding composition (PM), comprising the following steps:
[0076] a1) polymerization of at least one main monomer selected from cyclic formals and at least one first comonomer selected from formula (II) and optionally at least one second comonomer in the presence of an acid catalyst to provide a first mixture (M1) comprising a polyoxymethylene copolymer (cPOM) and an acid catalyst,
[0077]
[0078] Where R 1 To R 5 and n are as defined above,
[0079] b) adding triisopropanolamine to the first mixture (M1) to deactivate the acid catalyst to obtain a second mixture (M2) comprising a polyoxymethylene copolymer (cPOM) and a complex of the acid catalyst and triisopropanolamine,
[0080] c) optionally adding at least one additive to the second mixture (M2).
[0081] For steps a1) and b) of the process for preparing the polymer molding composition (PM), the above statements and preferences for the process for deactivating the acid catalyst in the process for preparing the polyoxymethylene copolymer (cPOM) apply analogously.
[0082] In step c), at least one additive is optionally added to the second mixture (M2). However, in a preferred embodiment, as described above, the second mixture (M2) contains 2 to 30% by weight of unreacted residual monomers and 50 to 700 ppm of a complex of a catalyst and triisopropanolamine. In addition, the polyoxymethylene copolymer may contain unstable end groups. Therefore, in a preferred embodiment, the second mixture (M2) is heat treated to remove residual monomers and depolymerize unstable end groups. The removal of residual monomers and unstable end groups is generally carried out in the melt using a kneading and degassing device. This finishing method is generally known to those skilled in the art.
[0083] To the final polyoxymethylene copolymer (cPOM) thus obtained, at least one additive may optionally be added.
[0084] The at least one additive can be added in any known device. Preferably the additive is added in a mixing device.
[0085] Suitable antioxidants are, for example, sterically hindered phenols, for example triethylene glycol bis(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, for example Irganox 245 from BASF SE. In the case of using antioxidants, they are added in such an amount that the polyoxymethylene copolymer (cPOM) comprises 0.001 to 10% by weight, preferably 0.002 to 5% by weight, more preferably 0.005 to 3% by weight, of antioxidant, based on the total weight of the polyoxymethylene copolymer (cPOM).
[0086] Suitable formaldehyde scavengers are, for example, amines, aminotriazine compounds, benzoguanamines, amino acids, hydrazides, ureas or urea derivatives, allantoin, guanamines, hydantoins, (modified) melamines or condensates of melamine and formaldehyde and polyamides, or mixtures thereof. In the case of using formaldehyde scavengers, they are added in such an amount that the polyoxymethylene copolymer (cPOM) contains 0.001 to 10% by weight, preferably 0.002 to 5% by weight, more preferably 0.005 to 3% by weight of formaldehyde scavengers, based on the total weight of the polyoxymethylene copolymer (cPOM).
[0087] Suitable polyamides are, for example, copolyamides based on caprolactam, hexamethylenediamine, bis(4-aminocyclohexyl)methane and adipic acid, which may also comprise monofunctional polymeric compounds such as propionic acid or triacetonediamine as components for regulating the molar mass. Examples are 1C and C31. In the case of using polyamide, it is added in such an amount that the polyoxymethylene copolymer (cPOM) contains 0.001 to 2 wt. %, preferably 0.005 to 1.99 wt. %, more preferably 0.01 to 0.08 wt. % of polyamide, based on the total weight of the polyoxymethylene copolymer (cPOM).
[0088] Suitable UV absorbers are, for example, hindered amine light stabilizers, for example polymeric hindered amines, wherein n is an integer from 5 to 50,
[0089]
[0090] When hindered amines are used, they are added in an amount such that the polyoxymethylene copolymer (cPOM) contains 0.001 to 10 wt %, preferably 0.002 to 5 wt %, more preferably 0.005 to 2 wt % of hindered amine, based on the total weight of the polyoxymethylene copolymer (cPOM).
[0091] Suitable release agents are, for example, esters or amides of saturated or unsaturated aliphatic carboxylic acids having 10 to 40 carbon atoms, preferably 16 to 22 carbon atoms, with polyols or aliphatic saturated alcohols or amines having 2 to 40 carbon atoms, preferably 2 to 6 carbon atoms. In the case of using esters or amides, they are added in such an amount that the polyoxymethylene copolymer (cPOM) contains 0.01 to 5% by weight, preferably 0.09 to 2% by weight and in particular 0.1 to 0.7% by weight of release agent, based on the total weight of the polyoxymethylene copolymer (cPOM). Preferred esters or amides are therefore glyceryl distearate, glyceryl tristearate, ethylenediamine distearate, glyceryl monopalmitate, glyceryl trilaurate, glyceryl monobehenate and pentaerythritol tetrastearate.
[0092] Suitable acid scavengers are, for example, alkali metal or alkaline earth metal carbonates, hydroxides, (hydroxy) stearates or silicates. In the case of using acid scavengers, they are added in such an amount that the polyoxymethylene copolymer (cPOM) comprises 0.001 to 2% by weight, preferably 0.002 to 1% by weight and in particular 0.003 to 0.7% by weight of acid scavenger, based on the total weight of the polyoxymethylene copolymer (cPOM).
[0093] Suitable nucleating agents are, for example, melamine cyanurate, melamine formaldehyde condensates, silicic acid, branched polyoxymethylenes and talc. In the case of using nucleating agents, they are added in such an amount that the polyoxymethylene copolymer (cPOM) contains 0.005 to 5% by weight, preferably 0.01 to 2% by weight and in particular 0.02 to 0.7% by weight of nucleating agent, based on the total weight of the polyoxymethylene copolymer (cPOM).
[0094] If present, additives are added in a customary manner, for example individually or together, in pure form, in the form of a solution or suspension or a masterbatch.
[0095] Another object of the present invention is a polymer molding composition (PM) comprising a polyoxymethylene copolymer (cPOM) and 50 to 700 ppm of a deactivated complex of a catalyst with triisopropanolamine, based on the total weight of the polymer molding composition (PM).
[0096] The polymer molding composition (PM) obtained by the process for preparing a polymer molding composition (PM) preferably comprises
[0097] 60 to 99.9% by weight of polyoxymethylene copolymer (cPOM),
[0098] 50 to 700 ppm of a complex of an acid catalyst and triisopropanolamine, and optionally
[0099] 0 to 39.99 wt % of at least one additive selected from antioxidants, formaldehyde scavengers, UV absorbers, mold release agents, acid scavengers, and nucleating agents.
[0100] A further object of the present invention is the use of the polymer molding composition (PM) for producing moldings.
[0101] The present invention is described in more detail by the following examples, but is not limited thereto.
[0102] Example
[0103] a. Analytical methods
[0104] Weight loss N2 (weight loss measured under nitrogen atmosphere):
[0105] To test thermal stability, the weight loss at 220° C. under N2 was determined. It is the percentage weight loss of a weighed sample of about 1.2 g of particles heated at 220° C. under nitrogen for 2 h. After cooling, the sample was weighed again and the weight loss was calculated.
[0106] MVR (DIN EN ISO 1133-1:2012-03):
[0107] The melt volume flow rate (MVR) is determined by extruding the molten material from the cylinder of the plastometer through a die of specified length and diameter under preset conditions of temperature (190°C) and load (2.16 kg).
[0108] Extractable formaldehyde (FA) content:
[0109] The content of extractable FA in cPOM particles was determined as follows. 50 g of cPOM particles and 70 ml of water were placed in a conical flask and stirred under reflux for 50 or 100 min. After rapid cooling, the FA content was determined on a Metrohm Titroprozessor 682. Therefore, n / 10 sodium hydroxide solution (5 ml) was used and then (if necessary) the pH value was adjusted to pH 9.4 using n / 10 sulfuric acid. Subsequently, 5 ml of sodium sulfite solution (136 g Na2SO3 dissolved in 1 kg of deionized water) was added. After the reaction of Na2SO3 and FA, the solution was back-titrated to pH 9.4 using n / 10 sulfuric acid.
[0110] The FA content was calculated as follows:
[0111] Mass of FA [mg] = H2SO4 consumed x 2 x H2SO4 concentration x formaldehyde mass
[0112] FA content [%] = mass of FA [mg] / net weight [g, cPOM particles] x (1 000 000 / 1000)
[0113] x represents the multiplication operator
[0114] Assume that the reaction follows the reaction scheme shown below
[0115]
[0116] Formaldehyde emission (VDA 275, 1994 edition, July 1, 1994):
[0117] The samples (test specimens) were prepared as follows: cPOM granules were molded into injection molded plaques (40 x 100 x 2.5 mm) in injection molding, and the following parameters were used in the injection molding machine: mass temperature: 200° C., tool wall temperature: 90° C. The test specimens were stored in PE bags before testing.
[0118] For the determination, the sample was fixed for a defined time in distilled water in a sealed (closed) 1 L polyethylene bottle at a constant temperature (60°C). Afterwards, the 1 L polyethylene bottle was cooled and the formaldehyde content in the distilled water was determined as follows. Photometric analysis using the so-called acetylacetone method was applied. Thus, formaldehyde was converted into diacetyldihydrolutidine using acetylacetone and ammonium acetate. The concentration of diacetyldihydrolutidine was measured photometrically (the maximum absorption wavelength of diacetyldihydrolutidine is 412 nm).
[0119] The formaldehyde content is given relative to the dry weight of the sample (mg / kg = ppm).
[0120] Tensile test (DIN EN ISO 527-2, Juni 2012):
[0121] The tensile bars were injection molded in an injection molding machine at a melt temperature of 200°C and a mold temperature of 90°C. The tensile tests were performed according to DIN EN ISO 527-2. The average values of tensile modulus, tensile stress at yield, tensile stress at break, elongation at yield, elongation at break and nominal elongation at break were obtained from ten tensile bars. Only type 1A specimens were used for all tensile tests.
[0122] Hydrolysis resistance (100℃):
[0123] The tensile test of the test strips after high-temperature storage in water at 100° C. was measured according to ISO 527. The average value of three tensile strips was obtained each time.
[0124] Thermal aging tensile test (140℃):
[0125] The tensile test of the test strips after high temperature storage in air at 140° C. was measured according to ISO 527. The average value of three tensile strips was obtained each time.
[0126] Charpy test (DIN EN ISO 179-1, November 2010):
[0127] Charpy Strip (80x 10x 4mm 3 ) was injection molded in an injection molding machine at a melt temperature of 200° C. and a mold temperature of 90° C. The Charpy test was carried out in accordance with DIN EN ISO 179-1. The Charpy impact strength values were obtained from ten Charpy bars.
[0128] Color of pellets (DIN EN ISO 11664-4, June 2012):
[0129] The color difference ΔE from a polyoxymethylene standard (L=90.4; a=-1.24 and b=0.54) was determined using the CIELAB formula according to ISO 116644-4. The measurements were made using CIE standard illuminant D65 and using an observation field of 10° angular separation.
[0130] Total carbon emission (TCE relative to VDA 277, 1995 edition, January 1, 1995):
[0131] Determination of the total carbon release relative to VDA 277. The injection-molded sheets (60 x 60 x 1 mm) were crushed and the weighed amount (1 g) was stored in a glass container (10 ml) at 120° C. in air at a pressure of 1013.25 mbar for 5 h. Subsequently, a defined amount of gas from the container was analyzed by headspace GC. The total carbon release was determined as μg carbon per gram of sample.
[0132] Specific migration of triethanolamine (DIN-EN-1186-3, July 2002):
[0133] The samples (test specimens) were prepared as follows: cPOM granules were molded into injection molded plaques (60 x 60 x 2 mm) in an injection molding machine using the following parameters: mass temperature: 200° C., tool wall temperature: 90° C. The test specimens were stored in PE bags before testing.
[0134] The specific migration of triethanolamine (TEOA) was determined by Fraunhofer IVV (Fraunhofer-Institut für Verfahrenstechnik und Verpackung), 85354 Freising according to the European norm EN 1186-3 under the following conditions:
[0135] Food simulant: 50% ethanol
[0136] Contact time and contact temperature: 2h / reflux (3 repeated contacts)
[0137] Contact area / volume: 0.56dm 2 / 50ml
[0138] The amount of triethanolamine migrated in the third contact with the simulant was quantified by using Fraunhofer IVV method 1.4069. The migration solution was diluted 1 / 10 and analyzed by LC-MS with a mixture of ammonium acetate and ethanol as a mobile agent. For detection, the molecular weight was selected in positive single reaction monitoring mode and the characteristic daughter ions were detected. Quantification was performed by external calibration. The detection limit of triethanolamine in this method was 0.13 mg / kg.
[0139] Specific migration of triisopropanolamine (DIN-EN-1186-3, July 2002):
[0140] Preparation of samples (test specimens): POM granules were molded into injection molded plaques (60 x 60 x 2 mm) in an injection molding machine using the following parameters: mass temperature: 200° C., tool wall temperature: 90° C. The test specimens were stored in PE bags before testing.
[0141] The specific migration of triethanolamine was determined by Fraunhofer IVV (Fraunhofer-Institut für Verfahrenstechnik und Verpackung), 85354 Freising according to the European norm EN 1186-3 under the following conditions:
[0142] Food simulant: 50% ethanol
[0143] Contact time and contact temperature: 2h / reflux (3 repeated contacts)
[0144] Contact area / volume: 0.56dm 2 / 50ml
[0145] The amount of triisopropanolamine (TIPOA) that migrated in the third contact with the simulant was quantified using Fraunhofer IVV method 1.378. The migration solution was diluted 1 / 10 and analyzed by LC-MS with a mixture of formic acid and methanol as a mobile agent. Quantification was performed by external calibration. The detection limit of triisopropanolamine in this method was 0.005 mg / kg.
[0146] Extractable Total Organic Carbon (TOC) / FA Content in Drinking Water
[0147] According to KTW Guidelines (version of March 7, 2016) = Guidelines for Hygienic Assessment of Organic Materials in Contact with Drinking Water, reported to the European Commission, No. 2013 / 470 / D, in compliance with Directive 98 / 34 / EEC. The KTW Guidelines contain test protocols and safety requirements for plastics and silicones in contact with drinking water. Extraction and analysis were performed by Hygiene-Institutdes Ruhrgebiets, Germany.
[0148] The samples (test specimens) were prepared as follows: cPOM pellets were molded into injection molded plaques (100 mm x 70 mm x 2.5 mm) in an injection molding machine using the following parameters: mass temperature: 200° C., tool wall temperature: 90° C. The test specimens were stored in PE bags before testing.
[0149] Migration test was performed at 85°C (hot water) according to Annex 3 of the KTW Guidelines. Surface area / volume ratio was 5 dm -1 .
[0150] The migration water samples were analyzed using the pipe parameters of DN ≥ 300 mm (conversion factor = 1d / dm).
[0151] The amount of extractable total organic carbon (TOC) was analyzed according to DIN EN 1484.
[0152] The amount of extractable formaldehyde (FA) in drinking water is determined as follows. 20 ml of the migration solution is placed in a flask, and 2 ml of the parafuchsin solution is added (preparation of the parafuchsin solution: dissolve 160 mg of parafuchsin in 24.0 ml of concentrated hydrochloric acid, and add distilled water to 100 ml). In addition, 2 ml of a freshly prepared sodium sulfite solution is added (preparation of the sodium sulfite solution: dissolve 50 mg of sodium sulfite in 50 ml of distilled water). The flask is filled to 25 ml with distilled water, sealed, and the flask is shaken manually. The flask is stored at 23°C for 90 min. During this time, formaldehyde is converted into a red-purple complex with sodium sulfite and parafuchsin. The concentration of the complex of this color is measured photometrically (the maximum absorption wavelength of the complex of this color is 578 nm).
[0153] Residual amount of deactivator in polymer
[0154] The samples (test specimens) were prepared as follows: cPOM pellets were molded into injection molded plaques (60 mm x 60 mm x 2 mm) in an injection molding machine using the following parameters: mass temperature: 200° C., tool wall temperature: 90° C. The test specimens were stored in PE bags before testing.
[0155] The sample was crushed and about 300 mg of the polymer was dissolved in 5 ml of 1,1,1,3,3,3-hexafluoro-2-propanol. Subsequently, a flask was filled to a total volume of 10 ml with a mixture of water and 1 mole of HCl (ratio 100 / 1), and the mixture was stirred to precipitate the polymer. Then, about 30 mg of methylamine-HCl was added as the internal standard for measurement. The mixture was filtered (pore size 0.45 μm), and the solution was analyzed by electrophoresis to determine the concentration of TIPOA or TEOA relative to the internal standard. Electrophoresis was performed using 5 mmol of 4-aminopyridine (in H2SO4, pH 3.4) as the cathode electrolyte, +25 kV voltage, 16 μA ampere current, and temperature 20 ° C.
[0156] b. Materials
[0157] The following components were used:
[0158] (1) Coarse cPOM
[0159] The crude cPOM was taken from a kneading reactor for the preparation of polyoxymethylene copolymers. To prepare the crude cPOM, 96.5% by weight of trioxane and 3.5% by weight of dioxolane were used, based on the total amount of monomers used. The crude cPOM contained, in addition to cPOM, 85 ppm of BF3xOEt2, 3% by weight of unconverted trioxane and 5% by weight of thermally unstable end groups, based on the total weight of the crude cPOM.
[0160] (2) Amines used for deactivation:
[0161] Triethanolamine: technical grade, GC content min. 99%, BASF SE
[0162] Triisopropanolamine: technical grade, GC content of at least 99%, BASF SE
[0163] (3) Additives:
[0164] Irganox 245FF / Ethylenebis(oxyethylene)bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate)(36443-68-2): Irganox 245FF from BASF SE
[0165] Synthetic magnesium silicate (1343-88-0)
[0166] Talc (14807-96-6): Hydrous magnesium silicate
[0167] EBS / N,N'-ethylenebis(stearamide) (110-30-5)
[0168] Double-terminated PA: PA6,66 copolymer from BASF SE (molecular weight 3000, made from caprolactam, hexamethylenediamine, adipic acid and propionic acid)
[0169] Amorphous 6I / 6T polyamide (25750-23-6) (copolyamide prepared from 1,3-phthalic acid, 1,4-phthalic acid and 1,6-hexamethylenediamine)
[0170] o Tg=125-130℃
[0171] o VZ=81-85ml / g (in H2SO4)
[0172] o COOH end group: 88-135mmol / kg
[0173] o NH2 end group: 40-42mmol / kg
[0174] Ca(OH)2 / Calcium hydroxide (1305-62-0)
[0175] Glyceryl Distearate(68308-54-3)
[0176] c. Preparation of materials
[0177] (1) Preparation of cPOM resin using different deactivators (pilot test):
[0178] The specific amine (triisopropanolamine or triethanolamine) was diluted with 20 g of water to promote uniform distribution in the crude cPOM (the amount of amine in the final cPOM is shown in Table 1). The deactivated solution was added to 10 kg of crude cPOM. The resulting mixture was kept for 30 min. Then 62 g of an additive mixture was added for further stabilization (the concentration of additives in the final product was: 0.35% Irganox 245FF, 0.05% synthetic magnesium silicate (1343-88-0), 0.15% distearic acid glyceryl, 0.04% double-end-capped PA and 0.05% talc). Afterwards, the mixture was extruded in a twin-screw extruder (TEX-30, L / D=40, Φ=27 mm) at 25 kg / h and 250 rpm. The melt temperature at the outlet was 200°C. The resulting granules were dried at 120°C for 6 h to obtain the final cPOM.
[0179] cPOM containing the following amines and concentrations were tested:
[0180]
[0181] Table 1
[0182] d. Results
[0183]
[0184] Table 2
[0185] The results in Table 2 show that the use of triisopropanolamine (TIPOA) to deactivate the catalyst resulted in lower FA content and lower FA release compared to triethanolamine (TEOA), a deactivator used in the prior art. In addition, the use of TIPOA had no negative impact on the color and physical properties of cPOM.
[0186] Table 3: Results of hydrolysis resistance at 100°C
[0187]
[0188] Table 3
[0189] Table 4: Results of heat aging tensile tests
[0190]
[0191] Table 4
[0192] The results in Tables 3 and 4 demonstrate that TIPOA imparts cPOM with improved hydrolysis and heat aging properties compared to TEOA.
[0193] (2) Preparation of cPOM resin using different deactivators (industrial scale test):
[0194] The crude cPOM was prepared in a kneader process using 85 ppm BF3*OEt2.
[0195] The ratio of dioxolane to trioxane used was 3.5:96.5 and the methylal was adjusted to produce a medium viscosity cPOM with a production of 1750 kg / h.
[0196] The amine used in the tests was metered in as a 6% by weight solution in ethyl acetate and sprayed onto the crushed cPOM.
[0197] Residual monomers and unstable end groups were removed on a twin-screw extruder at 230°C / 135 rpm.
[0198] Additives (final concentration in PM): 0.35% Irganox 245FF, 0.05% synthetic magnesium silicate (1343-88-0), 0.05% talc, 0.04% amorphous 6I / 6T polyamide (25750-23-6), 0.15% EBS, 0.02% Ca(OH)2
[0199] The following amines and concentrations were tested (Table 5):
[0200]
[0201] Table 5e. Results
[0202]
[0203]
[0204] Table 6
[0205] Table 7: Results of hydrolysis resistance at 100°C
[0206]
[0207] Table 7
[0208] Table 8: Results of heat aging tensile tests at 140°C
[0209]
[0210] Table 8.
Claims
1. A method for deactivating an acid catalyst in a method for preparing a polyoxymethylene copolymer (cPOM), wherein the method for deactivating the acid catalyst comprises the following steps: a) providing a first mixture (M1) comprising a polyoxymethylene copolymer (cPOM) and an acid catalyst, b) adding triisopropanolamine to the first mixture (M1) to deactivate the acid catalyst to obtain a second mixture (M2) comprising a polyoxymethylene copolymer (cPOM) and a complex of the acid catalyst and triisopropanolamine.
2. The method according to claim 1, wherein the polyoxymethylene copolymer (cPOM) comprises 60 to 99.99 mol % of -CH2O- repeating units and 0.01 to 40 mol % of repeating units of formula (I) Where R 1 To R 4 are each independently a hydrogen atom, a C1-C4-alkyl group or an alkoxy-substituted alkyl group having 1 to 4 carbon atoms, and R 5 is a chemical bond, -CH2-, -OCH2-, a C1-C4-alkyl-substituted or C1-C4-alkoxy-substituted methylene or a corresponding oxymethylene group, and n is 0 to 3.
3. The method according to claim 1 or 2, wherein step a) comprises the following steps: a1) polymerization of at least one main monomer selected from cyclic formals and at least one first comonomer selected from formula (II) and optionally at least one second comonomer in the presence of an acid catalyst to provide a first mixture (M1) comprising a polyoxymethylene copolymer (cPOM) and an acid catalyst, Where R 1 To R 5 and n is as defined above in claim 2.
4. The method according to claim 1 or 2, wherein the acid catalyst is at least one acid catalyst selected from the group consisting of boron trifluoride, a coordination complex of boron trifluoride and water, a coordination complex of boron trifluoride and a dialkyl ether, and catalytically active conversion products of the above acid catalysts.
5. The process according to claim 1 or 2, wherein the acid catalyst in step a) is present in an amount of 10 to 150 ppm, based on the total weight of the first mixture (M1).
6. The process according to claim 3, wherein the acid catalyst in step a1) is present in an amount of 10 to 150 ppm, based on the total weight of the main monomer and the comonomer.
7. The method according to claim 1 or 2, wherein the triisopropanolamine in step b) is added at a molar ratio of 25:1 to 1:1 relative to the acid catalyst.
8. The process according to claim 1 or 2, wherein in step b), triisopropanolamine is added in the form of a solution comprising triisopropanolamine dissolved in at least one solvent.
9. The method according to claim 8, wherein the solution comprises ethyl acetate as solvent.
10. Use of triisopropanolamine for deactivating an acid catalyst in the preparation of a polyoxymethylene copolymer, wherein the acid catalyst is complexed with the triisopropanolamine.
11. A method for preparing a polymer molding composition (PM), comprising the following steps: a1) polymerization of at least one main monomer selected from cyclic formals and at least one first comonomer selected from formula (II) and optionally at least one second comonomer in the presence of an acid catalyst to provide a first mixture (M1) comprising a polyoxymethylene copolymer (cPOM) and an acid catalyst, Where R 1 To R 4 are each independently a hydrogen atom, a C1-C4-alkyl group or an alkoxy-substituted alkyl group having 1 to 4 carbon atoms, and R 5 is a chemical bond, -CH2-, -OCH2-, a C1-C4-alkyl-substituted or C1-C4-alkoxy-substituted methylene or a corresponding oxymethylene group, and n is 0 to 3, b) adding triisopropanolamine to the first mixture (M1) to deactivate the acid catalyst to obtain a second mixture (M2) comprising a polyoxymethylene copolymer (cPOM) and a complex of the acid catalyst and triisopropanolamine, c) optionally adding at least one additive to the second mixture (M2).
12. Polymer molding composition (PM) obtainable by the process according to claim 11.
13. A polymer molding composition (PM) comprising a polyoxymethylene copolymer (cPOM) and 50 to 700 ppm, based on the total weight of the polymer molding composition (PM), of a deactivated complex of an acid catalyst with triisopropanolamine.
14. Use of the polymer molding composition (PM) according to claim 12 or 13 for producing moldings.
